2005 IEEE International Reliability Physics Symposium, 2005. Proceedings. 43rd Annual.
DOI: 10.1109/relphy.2005.1493185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure deuterium annealing on electrical and reliability characteristics of MOSFETs with high-k gate dielectric

Abstract: To completely passivate interface states o f high-k gate dielectric, we have developed a new high-pressure (up to IOOatm), pure (100%) hydrogen annealing system. Comparing with control (latm) forming gas (H>/A~40/0/96%) annealed sample, high pressure (S-20atm), pure H2 annealing of nMOSFET at 400°C shows 10-15% improvements of linear drain current (Id) and maximum transconductance (gm.ma,). Compared with hydrogen annealing, D2 annealed samples exhibit longer hot carrier lifetime. By optimizing process paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Recently, deuterium (D 2 ) and hydrogen (H 2 ) annealing has been used to improve the reliability and LFN properties of silicon devices, including nanowire FETs 7,8 . Several studies have reported that high-pressure annealing improves the electrical performance with the benefit of a short annealing time because of the high concentration of D 2 or H 2 gas within a particular space 9,10 . The binding energy of the Si-D bond is known to have a higher kinetic isotope effect than that of the Si-H bond.…”
mentioning
confidence: 99%
“…Recently, deuterium (D 2 ) and hydrogen (H 2 ) annealing has been used to improve the reliability and LFN properties of silicon devices, including nanowire FETs 7,8 . Several studies have reported that high-pressure annealing improves the electrical performance with the benefit of a short annealing time because of the high concentration of D 2 or H 2 gas within a particular space 9,10 . The binding energy of the Si-D bond is known to have a higher kinetic isotope effect than that of the Si-H bond.…”
mentioning
confidence: 99%